Non-covalent functionalization of graphene with poly(diallyl dimethylammonium) chloride: Effect of a non-ionic surfactant. (21st January 2015) - Kaur, Prabhsharan; Shin, Mun-Sik; Sharma, Neha; Kaur, Namarta; Joshi, Anjali; Chae, So-Ryong; Park, Jin-Soo; Kang, Moon-Sung; Sekhon, Satpal Singh
Abstract Carbon based nanomaterials (carbon nanotubes, graphene etc) containing various hetero atoms are promising metal free catalysts for oxygen reduction reaction in fuel cells. We report the non-covalent functionalization of graphene with poly(diallyl dimethylammonium) chloride (PDDA), a polyelectrolyte containing nitrogen, using a very simple method. The addition of a non-ionic surfactant (Triton X-100) during functionalization has been observed to improve the interactions between graphene and PDDA. An up-shift in the position of G-peak in the Raman spectra, down-shift in the binding energy (B.E.) of N1s peak and an up-shift in the B.E. of C1s peak in XPS spectra have been observed due to an inter-molecular charge-transfer from carbon in graphene to nitrogen in PDDA, which get enhanced in the presence of Triton X-100. Graphene functionalized with PDDA also show good thermal stability. The addition of a non-ionic surfactant enhances the non-covalent functionalization of graphene with PDDA, which is desirable from applications point of view.